Un pequeño gran problema: nuevos registros del ratón casero en Isla Socorro, México. - López-Higareda, Diana; Ríos-Muñoz, César; León-Paniagua, Livia (Instituto de Ecología, A.C., 2014)
We report new records of the house mouse (Mus musculus) collected in Socorro Island in the Mexican Pacific Ocean. These records contribute to extend the knowledge about the present range and possible causes of the presence of the species in different localities in the island.